PERAN KANTOR IMIGRASI KELAS IA SAMARINDA DALAM PENGAWASAN DAN PENINDAKAN ORANG ASING BERDASARKAN UNDANG – UNDANG NOMOR 6 TAHUN 2011 - Dina Paramitha Hefni Putri, Yenny Meilyana dan (Universitas 17 Agustus 1945 Samarinda, 2020)
In the implementation of surveillance and enforcement of foreigners in the East Kalimantan Region, Samarinda's Class I Immigration Office experienced a few obstacles including the presence, activities of foreigners, and abuse of residence permits of foreigners in the Samarinda area. The real weaknesses in the surveillance system do not lie solely on rules because the existing regulatory system is quite complete and clear, but lies in the limited number of officers possessed by the Class I Immigration Office A samarinda. Based on the background above, the writer wants to choose the title